Adoption of rural development policy decisions - Fernandez, Mario B. (FAO Regional Office for Latin America and the Caribbean SantiagoCL, 1984)
Analyzes factors which have affected rural development inter alia characteristics of development strategies applied and the effects of their applications on spatial localization of the population particularly the poorest groups; instruments of policy adopted and resulting desequilibria in development between urban and rural areas. Examines criteria for the orientation of a new development strategy and recommends changes for inclusion into macro-economic policies.